Phaeosphaeria chinensis sp. nov. (Phaeosphaeriaceae) with an asexual/sexual morph connection from GuangDong Province, China - Zhang, Ke-Ke; Hongsanan, Sinang; Tennakoon, Danushka S.; Tian, Sheng-Li; Xie, Ning (Phytotaxa, 2019)
Phaeosphaeria chinensis sp. nov. was found on dead leaves, collected from Guangdong Province, China. Morphology of the new species was compared with other Phaeosphaeria species and related genera of Phaeosphaeriaceae. Phylogenetic analyses of combined ITS, LSU, SSU and TEF-1 sequence data based on maximum parsimony (MP), maximum likelihood (ML) and Bayesian inference (BI) revealed that P. chinensis as a distinct species within the Phaeosphaeria with high bootstrap support. The comparison of the new species with other Phaeosphaeria species and a comprehensive description and micrographs are provided. The linkage of sexual and asexual morphs of the new species is also showed.